Some Formulas for Horn’s Hypergeometric Function GB of Three Variables - Ayman Shehata; Shimaa I. Moustafa; Jihad Younis; Hassen Aydi (Advances in Mathematical Physics)
Agarwal et al. (2021) established the extension of several fundamental contiguous relations for GB. Our aim in this work is to investigate several properties of differentiation formulas, differential equations, recursion relations, differential recursion relations, confluence formulas, series representations, integration formulas, and infinite summations for Horn’s hypergeometric function GB of three variables. Some well-known particular cases have additionally been given.